2008
DOI: 10.1007/s11205-008-9305-9
|View full text |Cite
|
Sign up to set email alerts
|

More Participation, Happier Society? A Comparative Study of Civil Society and the Quality of Life

Abstract: Subjective well-being, Quality of life, Satisfaction, Happiness, Quality of society, Good society, Participation in society, Voluntary associations, Civil society, European Social Survey, Multilevel analysis, Cross-national survey research,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
40
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 22 publications
7
40
1
1
Order By: Relevance
“…In contrast, civic participation in rural areas appeared to be generally at a lower level in the smallest settlement size category and showed inconsistent tendencies with the increase of a municipality's population size depending on the form of participation. A negative relationship between urbanization and civic participation was confirmed by an analysis of the European Social Survey that included data from 19 European countries [57]. In this analysis, suburbs, and in particular large cities, appeared to be negative, and country villages, and in particular countryside, to be positive predictors of civic participation, which was measured by the degree of involvement in 12 types of voluntary associations.…”
Section: Urbanization and Civic Participationmentioning
confidence: 63%
See 3 more Smart Citations
“…In contrast, civic participation in rural areas appeared to be generally at a lower level in the smallest settlement size category and showed inconsistent tendencies with the increase of a municipality's population size depending on the form of participation. A negative relationship between urbanization and civic participation was confirmed by an analysis of the European Social Survey that included data from 19 European countries [57]. In this analysis, suburbs, and in particular large cities, appeared to be negative, and country villages, and in particular countryside, to be positive predictors of civic participation, which was measured by the degree of involvement in 12 types of voluntary associations.…”
Section: Urbanization and Civic Participationmentioning
confidence: 63%
“…Further relevant individual predictors appeared to be home ownership [54], fulltime employment (negative), and length of residence [58]. The European Social Survey data that Wallace and Pichler [57] used for their study confirmed the role of the national or cultural context in the level of civic participation They found substantial differences between countries with high civic participation, such as Sweden, the Netherlands, Norway, Austria, and Denmark, and countries with low civic participation such as Spain, Portugal, Hungary, Poland, and Greece, which Lewicka [18] interpreted as a consequence of the value orientation (tradition vs. post-materialism) in these countries.…”
Section: Urbanization and Civic Participationmentioning
confidence: 96%
See 2 more Smart Citations
“…This permits us to examine the domain between individual subjective well-being and societal or national quality of life (Noll 2002) and allows the inclusion of local public services and indicators of downtown vitality into amenity determination. The majority of research on amenities is at the national level (for example, Diener and Suh 1997;Veenhoven 2005;Wallace and Pichler 2009), county level (Beale and Johnson 1998;Deller et al 2001Deller et al , 2005McGranahan 1999;Nord and Cromartie 1997;Veenhoven 2005), or commuter zone level of analysis (Goe and Green 2005). This is understandable given the greater availability of secondary data at these levels.…”
mentioning
confidence: 99%